Solve the equation. 5x + 6 = 2(2x – 3)

ANSWERS

2016-04-19 11:47:09

Isolate the variable on one side of the equation and everything else to the opposite side of the variable. You can isolate the variable by undoing the operations done to the variable. For example, if we added 5 to x (x + 5) then we would need to undo that operation. We would need to use the inverse of addition. Which is subtraction. 5x + 6 = 2(2x - 3) 5x + 6 = 4x - 6 <-- Distribute the 2 x + 6 = -6 <-- Subtract 4x from each side x = -12 <-- Subtract 6 from each side So, x is equal to -12.

ADD ANSWER